The Influence of Employee Competence and Performance on the Quality of Community Service at the One-Stop Investment and Integrated Service Office in Medan City - Herlina Agustina; Erika Revida; Hendra Dermawan Siregar (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study focuses on organizations that provide public services, such as Medan City Investment and One-Stop Integrated Services, which are examples of highly influential modern government agencies. This study aims to investigate how employee competence contributes to employee work performance at the Medan City Investment and One-Stop Integrated Service Office. This study uses a quantitative approach for analysis. A total of 126 participants from the Medan City One-Stop Investment and Integrated Services Office were included in this study. The method of obtaining data is used to analyze the questionnaire. Each statistical analysis used in this study includes validity and reliability tests, classical assumption tests, multiple regression analysis, hypothesis tests, and determination coefficients. The results of the study show that the variables of competence and staff work performance have a direct impact on the welfare of the general public in terms of service